Honduras : Unlocking Economic Potential for Greater Opportunities - Hernandez Ore, Marco Antonio; Sousa, Liliana D.; Lopez, J. Humberto (World Bank, Washington, DC, 2015)
Honduras is Central America’s second-largest country with a population of more than 8 million and a land area of about 112,000 square kilometers. The 20th century witnessed a profound economic transformation and modernization in Honduras. Honduras’ persistent poverty is the result of long-term low per capita growth and high inequality, perpetuated by the country’s high vulnerability to shocks. First, over the past 40 years the country has experienced modest growth rates marked by considerable volatility. Second, high levels of inequality have weakened the ability for growth to reduce poverty by limiting the extent to which a large segment of the population is able to fully access physical and human capital. Third, a large share of the population is vulnerable and exposed to regular shocks - both large and small which has exacerbated poverty by destroying or slowing asset accumulation. This systematic country diagnostic (SCD) explores the drivers of these development outcomes in Honduras, and reflects on the policy priorities that should underlie a development strategy focused on eradicating poverty and boosting shared prosperity. After identifying a number of critical factors affecting the country’s development outcomes, the SCD concludes that there is a need for a comprehensive agenda that tackles simultaneously the problems that have kept the country in a low development equilibrium for many decades, as well as emerging challenges that have the potential not only to prevent progress but also worsen the current situation. The SCD also argues that the policy agenda needs to be ambitious and move away from marginal interventions in order to move Honduras from a situation where its economic potentials are just potentials to another where they become actuals.